Intrinsic regulation of enteroendocrine fate by Numb. (22nd May 2017) - Sallé, Jérémy; Gervais, Louis; Boumard, Benjamin; Stefanutti, Marine; Siudeja, Katarzyna; Bardin, Allison J
Abstract: How terminal cell fates are specified in dynamically renewing adult tissues is not well understood. Here we explore terminal cell fate establishment during homeostasis using the enteroendocrine cells (EEs) of the adult Drosophila midgut as a paradigm. Our data argue against the existence of local feedback signals, and we identify Numb as an intrinsic regulator of EE fate. Our data further indicate that Numb, with alpha‐adaptin, acts upstream or in parallel of known regulators of EE fate to limit Notch signaling, thereby facilitating EE fate acquisition. We find that Numb is regulated in part through its asymmetric and symmetric distribution during stem cell divisions; however, its de novo synthesis is also required during the differentiation of the EE cell. Thus, this work identifies Numb as a crucial factor for cell fate choice in the adult Drosophila intestine. Furthermore, our findings demonstrate that cell‐intrinsic control mechanisms of terminal cell fate acquisition can result in a balanced tissue‐wide production of terminally differentiated cell types. Synopsis: Enteroendocrine cell replenishment in Drosophila intestine is required for gut homeostasis. Symmetric distribution of Notch inhibitor Numb during intestinal stem cell division and its de novo synthesis in the differentiating daughter cell, rather than paracrine signalling, are required for enteroendocrine cell specification. Local enteroendocrine feedback signaling does not alter enteroendocrine cell production in the intestine. Numb regulates cell lineage‐intrinsic decisions that control enteroendocrine cell differentiation. Numb is segregated both symmetrically and asymmetrically during intestinal stem cell division. Numb acts with AP‐2 to inhibit Notch signaling and promote enteroendocrine cell fate in one of daughter cells. De novo synthesis of Numb in the daughter cell, together with altered Numb distribution and inheritance during intestinal stem cell division, are essential for enteroendocrine cell specification. Abstract : Symmetric distribution of Numb during intestinal stem cell division as well as de novo synthesis in the differentiating daughter cell are required for enteroendocrine cell specification and homeostasis in the Drosophila intestine.